PERFORMANCE MEASUREMENTS OF EXPORT GARMENTS MANUFACTURING COMPANIES IN KARUR DISTRICT - M, Rajeshwari.; Rajkumar . A, Dunstan (International Journal of Psychosocial Rehabilitation, 2020)
Working capital is being considered as on one of the measures of an efficiency of the firm. It means the availability of cash to meet its day-to-day operations of any enterprise. It is also denoted as a benchmark of any firm’s short-term financial position. Each and every business has to plan effectively for the utilization of working capital. The firm has to maintain optimum level of working capital in order to maintain a balance between the profitability and liquidity of the firm. It should not maintain neither excessive nor deficit working capital. Both lead to affect the goodwill of the firm. This article may explain the performance measurements of working capital management and its impact on profitability of select export garment companies in Karur district (ie) Asian Fabricx Private Limited and Sri Laxmi Exports. To explore the relationship between the working capital management and profitability, eight variables are considered as independent variables like current ratio, total assets turnover ratio, fixed assets turnover ratio, debtors turnover ratio, working capital turnover ratio, average payment period, average collection period and cash collection period whereas Return on Assets are taken as dependent variable. Pearson’s correlation is taken as tool to examine its relationship exists between them. The investigation concludes the performance measurements of export garment manufacturing companies are significant.